Complex Terrain Mapping Integrated Use of Stereo Air Photos and Satellite Images - Rivard, Lambert; Hehner-Rivard, Carla; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
A review of five major categories of lithogenetic and morphogenetic terrain types meet the complex terrain criteria: landslides, field photos of slope failures, bedrocks, nonglacial surficial deposits, glacial and alpine-glacial, and periglacial. Interpretations are based on personal knowledge and available background materials. This monograph documents a concept of complex terrains with the use of 208 illustrations, including 64 analyzed and extensively commented examples of stereo-pair air photos and 64 related satellite images.
Preface -- Complex terrain -- Stereo air photos -- High resolution stereo satellite images -- Introduction -- Air photo layout format -- Regional setting satellite images -- Landslide types -- Field photos of slope failures -- Bedrock types -- Nonglacial surficial deposits -- Glacial and alpine-glacial types -- Periglacial types.
Keywords: Geography; Geographical information systems; Remote sensing; Geomorphology; Geography; Geographical Information Systems/Cartography.; Geomorphology; Remote Sensing/Photogrammetry.; Electronic books